THE EFFECT OF GRIT AND LEARNING MOTIVATION ON ACADEMIC PROCRASTINATION THROUGH ONLINE LEARNING ON STUDENTS OF MTS N 1 BANYUMAS - Nikmatul Maghfiroh; Zaldhi Yusuf Akbar (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study was aimed to determine the effect of grit and learning motivation on academic procrastination on students of Mts N 1 Banyumas who were doing online learning. The respondents for this study were eighth-grade students from Mts N 1 Banyumas, consisted of 84 students. The results of data analysis using multiple linear regression revealed that grit obtained an effect on academic procrastination, with t obs= -15.306 and the probability value of sig. (p) = 0.000 (p0.05), indicating that the hypothesis was accepted and the regression equation y = 141,415+(-607x) indicating that there was a significant effect. The result of the regression equation was y =121,697 +(- 0,597). The regression analysis of the effect of grit and learning motivation on academic procrastination obtained f obs= 131.445 and probability sig (p) = 0.000 (p0.05), indicating that grit and learning motivation had an effect on academic procrastination among Mts N 1 Banyumas students. The research obtained an R square of 0.764, indicating that grit and learning motivation successfully contributed 76.4% to academic procrastination, whereas 23.6% was a contribution from other factors not examined.